Impact of the WHO FCTC on non-cigarette tobacco products. (31st July 2018) - Zaatari, Ghazi S; Bazzi, Asma
Abstract : Introduction: This paper investigates to what extent Framework Convention on Tobacco Control (FCTC) parties have successfully implemented regulatory measures against non-cigarette tobacco product (NCTP) use, considers the challenges and peculiarities in applying such regulations and proposes effective means. Data and methods: This review was based on many sources mainly: International Legal Consortium, International Tobacco Control, Campaign for Tobacco-Free Kids, FCTC, expert group visits and published literature. Findings and conclusion: The FCTC provided a framework that applies to all forms of tobacco and this encouraged some parties to adopt control measures against NCTP and to incorporate them into their national tobacco control plans. Although a number of countries have adopted measures specifically targeted towards smokeless and waterpipe tobacco, greater global progress is needed. The strongest achievements have been in protection from exposure to tobacco smoke; controlling advertising, promotion and sponsorship; controlling sales to and by minors; education, communication and public awareness; and packaging and labelling of NCTP. Countries which adopted broad definitions of tobacco products have demonstrated encouraging trends in curbing their use. Future work should address the deep-rooted social acceptance of NCTP, the laxity in their control, their exclusion from regulations in some countries and the failure to subject them to increased taxation. Control measures should also specifically target the initiation risk to youth and adolescents and all factors that contribute to that such as banning flavourings and promotions through social media. Stronger global surveillance of NCTP use, tracking of policy implementation and evaluation of policy impact will provide important evidence to assist parties in fully implementing the FCTC to control their use.